INFLUENCE OF INTERNATIONAL MIGRATION OF LABOR FORCE ON THE ECONOMY OF KAZAKHSTAN - M.M. Valiyeva; O.V. Kopylova; D.T. Yessembekova; A.Zh. Bekmatova; A.A. Baimagambetov (Academic Journal of Physical and Chemical Sciences, 2019)
Today, Kazakhstan is an example of stability, relative prosperity and tranquility not only in Central Asia, but also in the CIS. Its standard of living is comparable to the Russian one and is an order of magnitude higher than that in Central Asian states. However, in the field of employment and migration in the country there are still certain problems. Migration mobility is an attempt to mobilize one’s own resources and those of a family, relatives, clan, diasporas, public institutions in places of origin and achievement to expand life opportunities, increase one’s status, and accelerate upward social mobility. International labor migration has become an integral part of the modern system of the world economy, the norm of existence of most states. The presence of foreign workers in the developed countries of the world has turned from a temporary phenomenon into a structural element of the economy.